Spatio-temporal effects of river regulation on habitat quality for Atlantic salmon fry. (December 2017) - Buddendorf, W.B.; Malcolm, I.A.; Geris, J.; Fabris, L.; Millidine, K.J.; Wilkinson, M.E.; Soulsby, C.
Highlights: Demonstrates value of developing process based understanding of flow regime effects. Flow regulation effect on salmon fry habitat quality is spatio-temporally complex. Flow rules need to consider seasonal flow preferences of conservation target species. Caution needed when using discharge variability as habitat quality indicator. Abstract: Many upland rivers in the Northern Hemisphere contain important habitat for Atlantic salmon ( Salmo salar L.). Owing to their sensitivity to environmental change, salmon are often used as bio-indicators. In Scotland, rivers containing potentially suitable habitat for salmon fry are often also regulated for hydropower. Regulated flow regimes can differ substantially spatially and temporally. Thus, where river management may be needed to maintain, restore, and protect their ecological functioning, this needs to be based on evidence of such spatio-temporal effects. This study investigated the effects of different types of river regulation on the hydraulic characteristics of downstream river reaches and the inferred consequences for salmon fry using hydraulic habitat quality models. The study focussed on the River Lyon (390 km 2 ), a tributary of the Tay (4587 km 2 ), Scotland, UK. Hydraulic habitat variability was assessed for three reach-scale sites with contrasting flow regimes characterised by (a) releases from hydropower generation, (b) compensation flow and (c) partly re-naturalised flow conditions. For each site, high resolution Digital Terrain Models (DTMs) were developed from bathymetric surveys and 2D hydraulic models were used to assess hydraulic characteristics. Discharge time series were used to simulate hydraulic conditions for regulated and simulated natural flows. Depth and velocity data were extracted from the hydraulic models and used to infer habitat quality using a habitat model developed for Atlantic salmon fry in similar-sized Scottish rivers. Results showed the effects of regulation can vary substantially within reaches and between seasons. Comparison to natural flow regimes suggested that flow alteration has a variable influence on habitat quality depending on the type of regulation and time of year. This work has improved understanding of the effects of regulation on biophysical processes and may also be useful for managing trade-offs between management, restoration, and societal benefits.